Revisiting the Basal Role of ABA – Roles Outside of Stress. (July 2019) - Yoshida, Takuya; Christmann, Alexander; Yamaguchi-Shinozaki, Kazuko; Grill, Erwin; Fernie, Alisdair R.
Abstract : The physiological roles of abscisic acid (ABA) as a stress hormone in plant responses to water shortage, including stomatal regulation and gene expression, have been well documented. However, less attention has been paid to the function of basal ABA synthesized under well-watered conditions in recent studies. In this review, we summarize progress in the understanding of how low concentrations of ABA are perceived at the molecular level and how its signaling affects plant metabolism and growth under nonstressed conditions. We also discuss the dual nature of ABA in acting as an inhibitor and activator of plant growth and development. Highlights: Structural and biological evidence suggests that ABA receptor complexes operate at basal, nonstress ABA levels. Basal ABA balances primary metabolism and leaf growth in arabidopsis. Low levels of ABA play opposite roles in different tissues, inhibitory effects on leaf emergence, and promotion of root growth. Basal ABA levels support plant growth and development via a beneficial effect on plants' water status, which comprises proper adjustment of stomatal aperture, stimulation of tissue hydraulic conductivity, and a positive regulatory role in xylem development.